Quantitative 3-D anatomy of the human vertebrae (Asian population) - Chua, Hu Chuan. (2008)
Motivated by the lack of literature in the quantitative anatomy of the human spinal column of the Asian population, a research using Asian cadavers was conducted. The significance of such study includes engineering modelling, design of spinal implants and analyses of individual vertebrae to better understand the morphological and mechanics of the human spine for better spinal management.